AQUARIUM PARK KALIMANTAN BARAT - Bagaskara, Galih; Zain, Zairin; Kalsum, Emilya (JMARS: Jurnal Mosaik Arsitektur, 2024)
The Kapuas River is one of the rivers that crosses the island of Kalimantan. The Kapuas River is home to more than 700 species of freshwater fish, some of which are considered rare and endangered. These rare species are caused by the loss of habitat, mostly due to human activities. One of the solutions to the problem is to create an educational conservation facility specializing in breeding endangered species. The design is carried out through several stages, including introduction, definition, preparation, analysis, synthesis, and evaluation. The result of the design is an aquarium conservation building dedicated to cultivating the rare species of the Kapuas River with the aim of reintroducing them to their natural habitat. The building's function is educational, emphasizing observation to educate the public about the importance of preserving animal habitats in their environment. The Aquarium Park design integrates the mangrove ecosystem into its design, using a futuristic architectural approach that harmoniously blends organic forms with nature, as well as integrating technology into human physiological aspects. The use of interactive technologies such as Augmented Reality and Virtual Reality is added to enhance the interaction experience within the building.